2018
DOI: 10.1002/cbic.201700664
|View full text |Cite
|
Sign up to set email alerts
|

NMR Study of Rcf2 Reveals an Unusual Dimeric Topology in Detergent Micelles

Abstract: The Saccharomyces cerevisiae mitochondrial respiratory supercomplex factor 2 (Rcf2) plays a role in assembly of supercomplexes composed of cytochrome bc (complex III) and cytochrome c oxidase (complex IV). We expressed the Rcf2 protein in Escherichia coli, refolded it, and reconstituted it into dodecylphosphocholine (DPC) micelles. The structural properties of Rcf2 were studied by solution NMR, and near complete backbone assignment of Rcf2 was achieved. The secondary structure of Rcf2 contains seven helices, o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 34 publications
2
11
0
Order By: Relevance
“…A short helix, SH1 (E90-K100), is situated between TM2 and TM3, and a second short helix with no well-defined location, SH2 (V211-F222), is positioned at the C terminus. The overall topology of the present structure is in excellent agreement with the results from our earlier study using PREs (Zhou et al, 2018a).…”
Section: Solution Structure Of the Rcf2 Dimer In Dpc Micellessupporting
confidence: 91%
See 4 more Smart Citations
“…A short helix, SH1 (E90-K100), is situated between TM2 and TM3, and a second short helix with no well-defined location, SH2 (V211-F222), is positioned at the C terminus. The overall topology of the present structure is in excellent agreement with the results from our earlier study using PREs (Zhou et al, 2018a).…”
Section: Solution Structure Of the Rcf2 Dimer In Dpc Micellessupporting
confidence: 91%
“…Article good approximation for the dimensions and chemical environment of a membrane bilayer (White and Wimley, 1999). The observed NOE contacts between Rcf2 and DPC are consistent with our previously reported results from PRE and hydrogendeuterium exchange experiments (Zhou et al, 2018a), which demonstrated that the charged TM5 is buried in DPC micelles.…”
Section: Ll Open Accesssupporting
confidence: 90%
See 3 more Smart Citations